Studi Faktor Penyebab Turnover dan Upaya Retensi SDM di Pesantren Al Muslim Bireuen - Sutisna, Ade jaya; Nurhayati, Nurhayati (Adaara: Jurnal Manajemen Pendidikan Islam, 2025)
This study investigates the factors contributing to employee turnover and retention strategies in Pesantren Al Muslim Bireuen, focusing on the unique dynamics of Islamic educational institutions. The research adopts a qualitative approach, utilizing in-depth interviews with 15 employees and document analysis to explore their experiences and perspectives. Findings reveal that key factors causing turnover include low job satisfaction, excessive workload, uncompetitive compensation, and limited career development opportunities. The study also highlights effective retention strategies such as improving employee welfare, providing career advancement programs, and fostering a supportive work culture. These findings align with Herzberg's two-factor theory and the Job Demand-Resource model, offering a nuanced understanding of turnover in the pesantren context. The research recommends implementing comprehensive strategies to enhance employee satisfaction and organizational commitment, including periodic training, competitive remuneration, and improved communication between management and staff. This study contributes to the existing literature by examining turnover in Islamic boarding schools, which remains underexplored in human resource management research. Limitations of the study include the single-site focus and relatively small sample size, suggesting the need for further research involving diverse pesantren across regions.